Origin and consequences of the debt crisis and ways of solving it - Jürgen Westphalen (Intereconomics, 1984)
In the 1970s Latin America accounted for a high, and constantly increasing, proportion of the total public foreign debt of all developing countries, reaching a share of 35% by the end of the decade. In comparison, Latin America's share of the total GDP of the developing countries is around 20%. The following article explains the specific causes of the debt crisis in Latin America and suggests some ways of overcoming it.
Keywords: 330; Latin America